Methods for development of structure, process and outcome indicators for prioritized spinal cord injury rehabilitation Domains: SCI-High Project. (30th September 2019) - Craven, B. Catharine; Alavinia, S. Mohammad; Wiest, Matheus J.; Farahani, Farnoosh; Hitzig, Sander L.; Flett, Heather; Jeyathevan, Gaya; Omidvar, Maryam; Bayley, Mark T.
Abstract : Background: High-quality rehabilitation care following spinal cord injury or disease (SCI/D) is critical for optimizing neurorecovery and long-term health outcomes. This manuscript describes the methods used for developing, refining, and implementing a framework of structure, process, and outcome indicators that reflect high-quality rehabilitation among adults with SCI/D in Canada. Methods: This quality improvement initiative was comprised of the following processes: (1) prioritization of care Domains by key stakeholders (scientists, clinicians, therapists, patients and stakeholder organizations); (2) assembly of 11 Domain-specific Working Groups including 69 content experts; (3) conduct of literature searches, guideline and best practice reviews, and outcome synthesis by the Project Team; (4) refinement of Domain aim and construct definitions; (5) conduct of cause and effect analysis using Driver diagrams; (6) selection and development of structure, process and outcome indicators; (7) piloting and feasibility analysis of indicators and associated evaluation tools; and, (8) dissemination of the proposed indicators. Result: The Project Team established aims, constructs and related structure, process, and outcome indicators to facilitate uniform measurement and benchmarking across 11 Domains of rehabilitation, at admission and for 18 months thereafter, among adult Canadians by 2020. Conclusion: These processes led to the selection of a feasible set of indicators that once implemented should ensure that adults with SCI/D receive timely, safe, and effective rehabilitation services. These indicators can be used to assess health system performance, monitor the quality of care within and across rehabilitation settings, and evaluate the rehabilitation outcomes of the population to ultimately enhance healthcare quality and equity.